Reputation: 3413
I'm curious about the expression flip id
(It's not homework: I found it in the getOpt
documentation).
I wonder why it has this type:
Prelude> :t (flip id)
(flip id) :: b -> (b -> c) -> c
For example, (flip id) 5 (+6)
gives 11
.
I know why id (+6) 5
gives 11, but I don't "get" the flip id
thing.
I tried to figure this out myself using pen and paper but couldn't. Could anybody please explain this to me? I mean, how does flip id
come to have the type b -> (b -> c) -> c
?
Upvotes: 50
Views: 2855
Reputation: 826
The id
function has this type:
id :: a -> a
You get an instance of this type, when you replace a
by a -> b
:
id :: (a -> b) -> (a -> b)
which, because of currying, is the same as:
id :: (a -> b) -> a -> b
Now apply flip
to this and you get:
flip id :: a -> (a -> b) -> b
In the case of id (+)
the instance is:
id :: (Num a) => (a -> a) -> (a -> a)
Now flip id
gives you:
flip id :: (Num a) => a -> (a -> a) -> a
Side note: This also shows you how ($)
is the same as id
, just with a more restricted type:
($) :: (a -> b) -> a -> b
($) f x = f x
-- unpoint:
($) f = f
-- hence:
($) = id
Upvotes: 81